Flora diversity and its potential in Muara Kendawangan Nature Reserve, West Kalimantan - TAHAN UJI (Biodiversitas Journal of Biological Diversity, 2003)
Muara Kendawangan Nature Reserve is one of the biggest nature reserves in West Kalimantan. However, data andinformations especially floras diversity and its potential in this area has not been investigated intensively. Two hundred andnineteen species of plant are collected from this area, and 140 species of them are reported as potential plants. Fourty eight, and fourty two species of the potential species are respectively useful as timber and medicinal plants. Six species, namely Aquilaria malaccensis, Durio oxleyanus, Eusideroxylon zwageri, Alstonia scholaris, Koompassia malaccensis and Eurycoma longifolia are threatened species, and one of them namely Aquilaria malaccensis is endangered.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: diversity, potential flora, Muara Kendawangan Nature Reserve, West Kalimantan.